2014
DOI: 10.1007/s10461-014-0902-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Scale of Perceived Social Support in HIV (PSS-HIV)

Abstract: Social support (SS) plays a key role for HIV/AIDS prevention and disease management. Numerous general and disease-specific SS instruments have been developed and perception of support has been increasingly considered, though no scales have been specifically developed to measure perceived social support (PSS) in HIV/AIDS. To help fill this gap a 12-item scale was developed. The study comprised 406 (HIV(+) and HIV(-)) participants from Chile and the UK. A principal component factor analysis yielded three factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 60 publications
3
16
0
1
Order By: Relevance
“…The studies that do include resilience resources specific to living with HIV mostly examine HIV-specific self-efficacy measures [(e.g., (Nokes et al, 2012;Wolf et al, 2007)]; very few studies include measures of social support specifically for PLWH or include neighborhood/community-level resilience resources specific to PLWH. While there are some published studies that have developed measures specific to PLWH, these studies mostly include measures developed at the individual level (e.g., HIV Self-Efficacy, healthrelated resilience, treatment optimism) (Brennan et al, 2009;Erlen, Cha, Kim, Caruthers, & Sereika, 2010;Renwick, Halpen, Rudman, & Friedland, 1999) while a few measure social support for PLWH (Cortes, Hunt, & McHale, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The studies that do include resilience resources specific to living with HIV mostly examine HIV-specific self-efficacy measures [(e.g., (Nokes et al, 2012;Wolf et al, 2007)]; very few studies include measures of social support specifically for PLWH or include neighborhood/community-level resilience resources specific to PLWH. While there are some published studies that have developed measures specific to PLWH, these studies mostly include measures developed at the individual level (e.g., HIV Self-Efficacy, healthrelated resilience, treatment optimism) (Brennan et al, 2009;Erlen, Cha, Kim, Caruthers, & Sereika, 2010;Renwick, Halpen, Rudman, & Friedland, 1999) while a few measure social support for PLWH (Cortes, Hunt, & McHale, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Social support has been posited as an essential variable for quality of life among PLWH (Remor et al, 2012) and in psychopathology prevention, with a well-documented inverse relationship between social support and anxiety and depression in PLWH (e.g., Heywood & Lyons, 2016;Rao et al, 2012). Concerning Spanish speakers, these same results have been found in Spaniards and Chileans (Carrobles Isabel, Remor Bitencourt, & Rodríguez Alzamora, 2003;Cortes, Hunt, & McHale, 2014). Studies have also found a direct relationship to positive mental health outcomes such as resilience in PLWH.…”
mentioning
confidence: 82%
“…Such tools can provide valuable data that are specific to each person's level of needs and context, which could then be utilized to devise strategies to enhance social support and decrease isolation. 26 All of the women in this study encountered a health care system that was very different from the one that they were accustomed to in their country of origin. Richter and colleagues 27 examined the use of peer support for pregnant women living with HIV infection.…”
Section: Implications For Clinical Practicementioning
confidence: 97%